2017
DOI: 10.1371/journal.pone.0169503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calf Gender on Milk Yield and Fatty Acid Content in Holstein Dairy Cows

Abstract: The scale of sexed semen use to avoid the birth of unwanted bull calves in the UK dairy industry depends on several economic factors. It has been suggested in other studies that calf gender may affect milk yield in Holsteins- something that would affect the economics of sexed semen use. The present study used a large milk recording data set to evaluate the effect of calf gender (both calf born and calf in utero) on both milk yield and saturated fat content. Linear regression was used to model data for first la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Additionally, in several other studies [ 11 , 26 , 30 , 31 ], mothers of female offspring also had higher milk yield, but these differences compared to the male sex differed depending on lactation order or cattle breed. Studies conducted by some of the researchers [ 10 ] also indicate slightly higher milk production in mother cows that calved female calves during four consecutive lactations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, in several other studies [ 11 , 26 , 30 , 31 ], mothers of female offspring also had higher milk yield, but these differences compared to the male sex differed depending on lactation order or cattle breed. Studies conducted by some of the researchers [ 10 ] also indicate slightly higher milk production in mother cows that calved female calves during four consecutive lactations.…”
Section: Discussionmentioning
confidence: 84%
“…The above authors suggest that the sex of the calf in utero affects the endocrine control of mammogenesis. It is generally accepted that prolactin and placental lactogens play an important role in mammogenesis and lactogenesis [ 22 , 23 , 24 , 25 , 26 ]. Prolactin, growth hormone, and placental lactogens form a group of structurally linked hormones, which probably evolved from a peptide that belonged to a common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sex of the fetus gestated on the first parity has persistent consequences for milk synthesis on the subsequent parity. Contrastingly, Gillespie et al [57] did not detect a significant effect of the sex of the calf being gestated on the mother milk production. Dallago et al [55].…”
Section: Bovine Sex-biased Milk Productionmentioning
confidence: 81%
“…According to the same study, the milk composition was similar whether the gestation produced a gestation of a son or daughter; the fat concentration was 3.61% after gestation of a daughter and 3.62% after gestation of a son; protein concentrations were the same (3.17%) [1]. Gillespie et al [57] also showed that, in the UK, calving a heifer was associated with a 1% milk yield advantage in first lactation heifers, but calving a bull calf conferred a 0.5% advantage in second lactation. Heifer calves were also associated with a 0.66 kg reduction in saturated fatty acid content of milk in first lactation, even though there was no significant difference between genders in the second lactation.…”
Section: -2017mentioning
confidence: 90%
See 1 more Smart Citation